The Concept of the Canonical Prescription. Legal Comparison and Theoretical Observations on can. 197 CIC/83 (can. 1540 CCEO), with Particular Consideration of the Polish Canonized Law - SKONIECZNY, PIOTR (Prawo Kanoniczne, 2013)
The author studies the concept of the canonical prescription in relation to Polish civil law. He notes straightaway that the term “praescriptio” found in the title of Book I, Title X and in canons 198 and 199 of the 1983 Code of Canon Law does not have the same meaning as we find in canon 197, because the latter confines itself to what is in civil law (to the so-called “dawność” in Polish). He therefore intends not to translate it into Polish or to add the adjective “canonical” to the word “prescription”. He then analyses the various models of prescription to be found in civil law systems, and he criticises the term “iuris subiectivi” as the object of prescription as stated in canon 197 of the 1983 Code. According to the author, the transfer of canon 197 of the 1983 Code from Book V is a mistake.